Розвиток інституту дипломатичного захисту фізичних і юридичних осіб - Крилов, Максим Анатолійович (Одеса, 2021)
Дисертація присвячена дослідженню становлення дипломатичного захисту як інституту сучасного міжнародного права.

У роботі простежено історію становлення інституту дипломатичного захисту, досліджено поняття інституту дипломатичного захисту; виявлені проблеми, що виникають при здійсненні дипломатичного захисту осіб, які мають подвійне громадянство, та осіб без громадянства; зроблений аналіз проекту статей Комісії міжнародного права про дипломатичний захист.

Виокремлено державоцентриський підхід – як виключно дискреційне право держави на здійснення дипломатичного захисту, та антропоцентриський підхід до дипломатичного захисту, який передбачає позитивний обов’язок держави щодо надання дипломатичного захисту.

Обґрунтовано, що в основі дипломатичного захисту лежить компроміс між двома конфліктуючими принципами: персональним верховенством і територіальним верховенством держав. У зв’язку з цим було запропоновано авторське визначення дипломатичного захисту як комплексу заходів, визнаних згідно з міжнародним правом, за допомогою яких держава діє в умовах розширеної юрисдикції щодо своїх громадян з метою захисту своїх прав при дотриманні встановлених необхідних умов.

Доведено, що еволюція правил, які стосуються дипломатичного захисту, показує, що в процесі становлення правил дипломатичного захисту враховувалися різні, часом конкуруючі інтереси, однак основними є інтереси держави громадянства.

Проаналізовано Проекти статей про дипломатичний захист, підготовлені Комісією міжнародного права ООН, які повністю відповідають традиційному погляду на правову природу цього інституту, таким чином, Комісія міжнародного права ООН зробила серйозний недогляд в можливості узгодити дипломатичний захист з антропоорієнтованою еволюцією міжнародного права і тим самим послаблює роль дипломатичного захисту як засобу забезпечення дотримання прав людини.

The dissertation is devoted to the study of the development of diplomatic protection as an institution of modern international law.

The work traces the history of the formation of the institute of diplomatic protection, investigates the concept of the institute of diplomatic protection; analyzed the sources of the institute of diplomatic protection; identifies the problems arising in the implementation of diplomatic protection of persons with dual citizenship and stateless persons; analyses the UN International Law Commission Draft Articles on Diplomatic Protection.

The international legal system has undergone significant changes in recent decades, especially concerning substantive and procedural rights granted to individuals under international law. However, these developments not only do not replace or make diplomatic protection an obsolete institute, as some scholars and politicians have argued, but have revived the importance of diplomatic protection as a means of protecting such individual rights and challenged the traditional notions underlying such a mechanism.

The topic of the research, its purpose and tasks, the specifics of the object and the subject determined its methodological basis. The use of historical and dialectical methods made it possible to analyze the various stages of the formation of norms on diplomatic protection and its formation as an institute of international law. Based on the system method, the content of the concept of diplomatic protection, its relationship with other concepts was considered. The formal-legal method was used for the legal analysis of the provisions of international legal acts regulating the procedure of diplomatic protection, as well as the analysis of normative-legal acts of Ukraine and other states regulating the procedure of diplomatic protection. The method of forecasting was used in considering the impact of anthropo-oriented evolution of the international legal system on the essence of diplomatic protection. Such logical methods of scientific cognition as induction, deduction, analogy, abstraction and concretization were also reflected in the work.

The paper highlights the state-centric approach – as the sole discretion of the state to exercise diplomatic protection, and the anthropocentric approach to diplomatic protection, which provides a positive obligation of the state on diplomatic protection.

It is substantiated that the basis of diplomatic protection is a compromise between two conflicting principles: personal supremacy and territorial supremacy of states. In this regard, the author proposed the author’s definition of diplomatic protection as a set of measures recognized in accordance with international law, with the help of which the state acts under conditions of expanded jurisdiction over its citizens in order to protect its rights, subject to the established necessary conditions. The undeniable connection of diplomatic protection with the responsibility of the state is emphasized, since it is necessary to highlight the conditions of responsibility of another state in terms of attribution of violation of the rights of a foreign citizen, as well as the exhaustion of internal protection mechanisms.

It is proved that the evolution of the rules concerning diplomatic protection shows that in the process of establishing the rules of diplomatic protection, different, sometimes competing interests were taken into account. As the rules of diplomatic protection evolved, the interests of the injured foreigner were reflected as well as the interests of the respondent State (for example, rules on the exhaustion of local remedies).

It is concluded that the Draft articles on diplomatic protection, prepared by the UN International Law Commission, fully comply with the traditional view of the legal nature of this institute, stating that “the right of diplomatic protection belongs to the state”, and thus, the UN International Law Commission made a serious omission in the opportunity to agree on diplomatic protection with the anthropo-oriented evolution of international law and thus weakens the role of diplomatic protection as a means of ensuring the observance of human rights.

The dualistic (from the point of view of whether it is a right or a duty of the state) legal nature of diplomatic protection is revealed: according to international law, the exercise of diplomatic protection is a discretionary right of the state; according to domestic law, the state is obliged to exercise diplomatic protection of its citizens, it follows from the legal connection between the state and the citizen (citizenship) and concerning other categories of persons (stateless persons, refugees), this is the right of the state since in this case there is such a strong legal connection as citizenship absent, however, the state has the right to establish in domestic law its duty to provide such protection to these categories of persons.

The main preconditions for the exercise of diplomatic protection are disclosed, without which the exercise of diplomatic protection is impossible due to the legal nature of this phenomenon or it will be considered illegal: 1) the existence of an internationally wrongful act that causes harm to a person in the territory of a foreign state; 2) the exhaustion of domestic remedies by the injured person on the territory of the receiving state where he was harmed; 3) the existence of a legal link between the applicant state and the injured person.

It is substantiated that international law already recognizes the existence of a certain obligation of the state to exercise diplomatic protection of a citizen who has suffered serious damage abroad. If customary international law has not yet reached this stage of development, then subparagraph (a) of Article 19 of the Draft Articles on diplomatic protection (article 19 “Recommended Practice”) should be considered as a progressive development of the law of diplomatic protection.
Крилов М. А. Розвиток інституту дипломатичного захисту фізичних і юридичних осіб. – На правах рукопису. Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.11 – міжнародне право. – Національний університет «Одеська юридична академія», МОН України, Одеса, 2021.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; дипломатичний захист; дискреційне право; антропоорієнтована еволюція міжнародного права; делегований дипломатичний захист; Комісія міжнародного права ООН; вичерпання місцевих засобів захисту; права людини; diplomatic protection; discretionary law; the anthropo-oriented evolution of international law; delegated diplomatic protection; the UN International Law Commission; the exhaustion of local remedies; human rights; дипломатическая защита; дискреционное право; антропоориентированная эволюция международного права; делегированная дипломатическая защита; Комиссия международного права ООН; исчерпание местных средств защиты; права человека